New combinations in Craterostigma and Torenia (Linderniaceae) from Asia with key to allied species - Liang, Yi-Shuo; Wang, Jenn-Che (Phytotaxa, 2016)
Traditionally, Lindernia s.l. Allioni (1766: 178) was the largest genus within Linderniaceae, with about 100 species, including members of Bonnaya Link & Otto (1820: 25), Ilysanthes Rafinesque (1820: 13), and Vandellia Linnaeus (1767: 384) (Pennell 1935, Rahmanzadeh et al. 2005). This concept (Pennell 1935) was adopted by subsequent taxonomists (e.g., Philcox 1968, Tsoong & Ku 1979, Yamazaki 1981, Fischer 1992, Lewis 2000, Liang et al. 2012) until Fischer et al. (2013), based on molecular and morphological evidence, proposed a more restrict circumscription of Lindernia s.str., separated from Bonnaya, Vandellia, Craterostigma Hochstetter (1841: 668), Crepidorhopalon Fischer (1989: 443), Torenia Linnaeus (1753: 619), and the new genus Linderniella Fischer et al. (2013: 227).